Coppper vapour laser treatment of cafe-au-lait macules - Kunachak Somyos (2018)
Cafe-au-lait macules are skin lesions known to resist all kinds of treatment. Green light at a wavelength of 511 nm from a copper vapour laser through a built-in computerized scanner (SCANALL) was employed to treat cafe-au-lait-macules in 16 patients. The laser was used in continuous mode with a mean energy density of 8.9 J/cm2(range 7-22 J/cm2). The mean number of treatment sessions was two. The response was good to excellent in 15 cases and poor in one. Transient hyperpigmentation at the periphery and temporary non-homogeneous hypopigmentation at the centre of the treated area was observed in some cases. These eventually returned to normal after a few months, without any textural change. Pre- and postoperative histological finding are also presented. There was no recurrence at a mean follow-up time of 22 months. Copper vapour laser is an effective modality for the treatment of cafe-au-lait macules.